Iridium(iii) phosphors with bis(diphenylphorothioyl)amide ligand for efficient green and sky-blue OLEDs with EQE of nearly 28%. Issue 33 (15th August 2018) - Xia, Jing-Cheng; Liang, Xiao; Yan, Zhi-Ping; Wu, Zheng-Guang; Zhao, Yue; Zheng, You-Xuan; Zhang, Wen-Wei
Abstract : A ligand, bis(diphenylphorothioyl)amide, containing phosphorus–sulfur (PS) bonds was synthesized as an ancillary ligand for four green or sky-blue iridium(iii ) complexes with high quantum yields, good thermal stabilities and satisfactory device performances with EQE of nearly 28%. Abstract : In this study, a new ligand, bis(diphenylphorothioyl)amide (Stpip), containing phosphorus–sulfur (PS) bonds was synthesized as an ancillary ligand. Four iridium(iii ) complexes (Ir(ppy)2 (Stpip), Ir(tfppy)2 (Stpip), Ir(ttppy)2 (Stpip) andIr(tntppy)2 (Stpip) with phenylpyridine derivates (ppy = 2-phenylpyridine); tfppy = 2-[4-(trifluoromethyl)phenyl]pyridine; ttppy = 2-[3, 5-bis(trifluoromethyl)phenyl]pyridine; tntppy = 2-[2, 6-bis(trifluoromethyl)-4-pyridyl]pyridine) as the main ligands were investigated. Due to the stable S–Ir bonds, these complexes emitted green or sky-blue photoluminescence with high quantum yields (Ir(ppy)2 (Stpip) : λ max = 490 nm, Φ = 44.7%;Ir(tfppy)2 (Stpip) : λ max = 495 nm, Φ = 85.4%;Ir(ttppy)2 (Stpip) : λ max = 477 nm, Φ = 92.1%;Ir(tntppy)2 (Stpip) : λ max = 516 nm, Φ = 90.8%) and good thermal stability. Using these compounds as emitters, all organic light-emitting devices (OLEDs) showed satisfactory performances. Notably, the device with theIr(tfppy)2 (Stpip) emitter achieved a maximum luminance of 37 321 cd cm −2 as well as maximum current efficiency, power efficiency and external quantum efficiency of 61.7 cd A −1, 48.5 lm W −1 and 21.8%, respectively. Moreover, the device with theIr(ttppy)2 (Stpip) complex exhibited the highest EQE value of nearly 28%. These results showed that bis(diphenylphorothioyl)amide is a promising ancillary ligand for efficient phosphorescent Ir(iii ) complexes and OLEDs.